Prevalence and types of high-risk human papillomaviruses in head and neck cancers from Bangladesh - Mushfiq H. Shaikh; Aminul I. Khan; Anwar Sadat; Ahmed H. Chowdhury; Shahed A. Jinnah; Vinod Gopalan; Alfred K. Lam; Daniel T. W. Clarke; Nigel A. J. McMillan; Newell W. Johnson (BMC Cancer, 2017)
Abstract Background There is a dramatic rise in the incidence of Human papillomavirus (HPV) – associated head and neck squamous cell carcinoma (HNSCC) in the world, with considerable variation by geography, gender and ethnicity. Little is known about the situation in Bangladesh, where tobacco- and areca nut-related head and neck cancers (HNCs) are the most common cancers in men. We aimed to determine the prevalence of HPV in HNSCC in Bangladesh and to explore the possible value of cell cycle markers in clinical diagnostic settings. Methods One hundred and ninety six archival HNSCC tissue samples were analysed for the presence of HPV DNA. The DNA quality was assured, and then amplified using a nested PCR approach. The typing of HPV was performed by automated DNA sequencing. Cellular markers p53, Cyclin D1 and pRb were tested on all samples by immunohistochemistry (IHC), as well as p16 as a putative surrogate for the detection of HPV. Results HPV DNA was detected in 36/174 (~21%) samples: 36% of cancers from the oropharynx; 31% of oral cancers, and 22% from the larynx. HPV-16 was most common, being present in 33 samples, followed by HPV-33 (2 samples) and HPV-31 (1 sample). Twenty-eight out of 174 samples were positive for p16, predominantly in HPV-positive tissues (p < 0.001). No statistically significant association was observed between the cellular markers and HPV DNA positive cases. However, p16 positivity had excellent predictive value for the presence of HPV by PCR. Conclusion There is a significant burden of HPV-associated HNSCC in Bangladesh, particularly in the oropharynx but also in oral and laryngeal cancers. Whilst a combination of PCR-based DNA detection and p16 IHC is useful, the latter has excellent specificity, acceptable sensitivity and good predictive value for carriage of HPV in this population and should be used for prognostic evaluation and treatment planning of all HNSCC patients in South Asia, as in the Western world.